2012
DOI: 10.1016/j.actbio.2012.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Human corneal limbal epithelial cell response to varying silk film geometric topography in vitro

Abstract: Silk fibroin films are a promising class of biomaterials that have a number of advantages for use in ophthalmic applications due to their transparent nature, mechanical properties and minimal inflammatory response upon implantation. Freestanding silk films with parallel line and concentric ring topographies were generated for in vitro characterization of human corneal limbal-epithelial (HCLE) cell response upon differing geometric patterned surfaces. Results indicated that silk film topography significantly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 50 publications
(63 reference statements)
2
61
0
Order By: Relevance
“…[32] Moreover, human corneal stromal stem cells cultured on such RGD modified films in serum-free keratocyte differentiation medium successfully differentiated into keratocytes, secreting multilayered lamellae with orthogonally-oriented collagen fibrils, in a pattern mimicking human corneal stromal tissue. [34] Likewise, human corneal limbal epithelial cells aligned on silk films with micrometer scale grooves, while also enhancing cell-to-cell contact formation, actin cytoskeleton alignment and focal adhesion localization [35]; and analogous patterns were found to direct the migration of limbalepithelial cells cultured as sheets. [36] Other nervous tissues such as the brain also contain regions with aligned cells, and patterned silk films with surface micro-grooves of 3 μm in width and 0.5 μm depth have dimensions that are analogous to the dimensions of cortical axons (0.3-1 μm) and glial cell processes (2-3 μm).…”
Section: Introductionmentioning
confidence: 96%
“…[32] Moreover, human corneal stromal stem cells cultured on such RGD modified films in serum-free keratocyte differentiation medium successfully differentiated into keratocytes, secreting multilayered lamellae with orthogonally-oriented collagen fibrils, in a pattern mimicking human corneal stromal tissue. [34] Likewise, human corneal limbal epithelial cells aligned on silk films with micrometer scale grooves, while also enhancing cell-to-cell contact formation, actin cytoskeleton alignment and focal adhesion localization [35]; and analogous patterns were found to direct the migration of limbalepithelial cells cultured as sheets. [36] Other nervous tissues such as the brain also contain regions with aligned cells, and patterned silk films with surface micro-grooves of 3 μm in width and 0.5 μm depth have dimensions that are analogous to the dimensions of cortical axons (0.3-1 μm) and glial cell processes (2-3 μm).…”
Section: Introductionmentioning
confidence: 96%
“…In some research works, silk fibroin films were used as wound dressing materials [103][104][105]. They are of particular biomaterials, which have wide range of applications in ophthalmic diseases due to their transparent nature, mechanical properties, and least possible inflammatory response upon implantation.…”
Section: Surface Nanofeaturesmentioning
confidence: 99%
“…They have also been processed in micron-nanosized fiber forms to direct stromal cell organization and differentiation in vitro, resulting in stratified collagen fibril lamellae in orthogonal orientations. A fibrous poly(ester urethane) urea substrate in combination with the use of human stromal stem cells, which are able to differentiate toward keratocyte lineages, showed promise for the in vitro engineering of the stroma via a two-dimensional (2D) approach, Immortalized human corneal epithelial cells Li et al, 15 Griffith et al, 79 Lawrence et al, 45 and Kitazawa et al…”
Section: Corneal Stromamentioning
confidence: 99%
“…44 Particularly, silk film topography significantly influenced initial human epithelial cell attachment, proliferation, and growth. 45,46 Further studies have shown that silk surfaces can be optimized by contact guidance to direct collective epithelial cell migration and the direction of tissue epithelialization. 47 Similarly, keratin-based substrates have been exploited for ocular surface reconstruction because of their good optical properties and ability to support epithelial cell growth in vitro.…”
Section: Corneal Epitheliummentioning
confidence: 99%